MANAGEMEN ERGONOMI - Bakri (UNIBA Surakarta), Solichul Hadi A (Manajemen Bisnis Syariah, 2011)
Ergonomi from the Greece language Which consists of word: “Egon”means work and “Nomos” means regulation as law. The term tobe used inskandinavia as “Biotechnoogy, in USA “Human Engineering”.The purpose of ergonomy implementation are: 1). Evaluating physical andmental welfare 2). Evaluating social welfare and 3). Creating rational balanceamong some aspects. Aspects to considered in ergonomy are: Age, set(male/female), body shapes and nutrition, physical fitness and phsycal workperformance.Keyword: ergonomy, worl, performance